Exercise in type 2 diabetes: genetic, metabolic and neuromuscular adaptations. A review of the evidence. Issue 21 (13th May 2017) - Zanuso, Silvano; Sacchetti, Massimo; Sundberg, Carl Johan; Orlando, Giorgio; Benvenuti, Paolo; Balducci, Stefano
Abstract : The biological responses to exercise training are complex, as almost all organs and systems are involved in interactions that result in a plethora of adaptations at the genetic, metabolic and neuromuscular levels. To provide the general practitioner and the sports medicine professionals with a basic understanding of the genetic, metabolic and neuromuscular adaptations at a cellular level that occur with aerobic and resistance exercise in subjects with type 2 diabetes. For each of the three domains (genetic, metabolic and neuromuscular), the results of the major systematic reviews and original research published in relevant journals, indexed in PubMed, were selected. Owing to limitations of space, we focused primarily on the role of skeletal muscle, given its pivotal role in mediating adaptations at all levels. Generally, training-induced adaptations in skeletal muscle are seen as changes in contractile proteins, mitochondrial function, metabolic regulation, intracellular signalling, transcriptional responses and neuromuscular modifications. The main adaptation with clinical relevance would include an improved oxidative capacity derived from aerobic training, in addition to neuromuscular remodelling derived from resistance training. Both training modalities improve insulin sensitivity and reduce cardiovascular risk. Taken together, the modifications that occur at the genetic, metabolic and neuromuscular levels, work correlatively to optimise substrate delivery, mitochondrial respiratory capacity and contractile function during exercise.